Intangible Heritage, Community and Family in the Anthroponymy of the Interior of Galicia (17th-19th centuries) - González López, Tamara (Madrygal. Revista de Estudios Gallegos, 2019)
The name constituted an intangible heritage which was received in the baptism; also, it became a principal part of newborn’s identity. The circumstances had influence the choice of the name, so the repertoire was changing just as the context; but, the name always conserved the symbolism about blood and spiritual family and of the community in where the baptised was born. It wasn’t a simple assignment of a name because the name used to be transmitted by a person close to the baptised, as an intangible gift and a demonstration of the relationship. The evolution of onomastic repertoire of the interior of Galicia can be showed when we analyze the transmission ways and their impact; also, it illustrated the importance of the family and the community in anthroponymy’s tendencies. In addition, it contributed to explain the reasons for the fast incorporation of certains names which didn’t belong to galician traditional repertoire, just as the refusal of others.
Keywords: Intangible Heritage; Anthroponymy; Lugo; Family; Baptism; Godparenthood